A Metabolomics and Molecular Networking Approach to Elucidate the Structures of Secondary Metabolites Produced by Serratia marcescens Strains - Clements, Tanya; Rautenbach, Marina; Ndlovu, Thando; Khan, Sehaam; Khan, Wesaal (Frontiers in Chemistry, 2021)
An integrated approach that combines reverse-phase high-performance liquid chromatography (RP-HPLC), electrospray ionization mass spectrometry, untargeted ultra-performance liquid chromatography coupled to tandem mass spectrometry (UPLC-MSE) and molecular networking (using the Global Natural Products Social molecular network platform) was used to elucidate the metabolic profiles and chemical structures of the secondary metabolites produced by pigmented (P1) and non-pigmented (NP1) Serratia marcescens (S. marcescens) strains. Tandem mass spectrometry-based molecular networking guided the structural elucidation of 18 compounds for the P1 strain (including 6 serratamolides, 10 glucosamine derivatives, prodigiosin and serratiochelin A) and 15 compounds for the NP1 strain (including 8 serratamolides, 6 glucosamine derivatives and serratiochelin A) using the MSE fragmentation profiles. The serratamolide homologues were comprised of a peptide moiety of two L-serine residues (cyclic or open-ring) linked to two fatty acid chains (lengths of C10, C12, or C12:1). Moreover, the putative structure of a novel open-ring serratamolide homologue was described. The glucosamine derivative homologues (i.e., N-butylglucosamine ester derivatives) consisted of four residues, including glucose/hexose, valine, a fatty acid chain (lengths of C13 – C17 and varying from saturated to unsaturated) and butyric acid. The putative structures of seven novel glucosamine derivative homologues and one glucosamine derivative congener (containing an oxo-hexanoic acid residue instead of a butyric acid residue) were described. Moreover, seven fractions collected during RP-HPLC, with major molecular ions corresponding to prodigiosin, serratamolides (A, B, and C), and glucosamine derivatives (A, C, and E), displayed antimicrobial activity against a clinical Enterococcus faecalis S1 strain using the disc diffusion assay. The minimum inhibitory and bactericidal concentration assays however, revealed that prodigiosin exhibited the greatest antimicrobial potency, followed by glucosamine derivative A and then the serratamolides (A, B, and C). These results provide crucial insight into the secondary metabolic profiles of pigmented and non-pigmented S. marcescens strains and confirms that S. marcescens strains are a promising natural source of novel antimicrobial metabolites.